Expectation-based types of voluntary sports clubs in regional sports federations - Schulz, Luc; Parensen, Andreas; Schlesinger, Torsten (Frontiers in Sports and Active Living, 2023)
Sports federations as non-profit organizations play a crucial role for organized sports activities of the population. However, one key responsibility of sports federations is providing needs-based support services to affiliated member sports clubs. Due to limited resources and simultaneously increasing heterogeneous expectations from their member sports clubs, designing an appropriate service portfolio poses increasing difficulties for sports federations. This study addresses these challenges by analyzing member clubs’ expectations and identifying distinct expectation types to enable more individually designed services. To analyze the expectations of member clubs (n=354), the explorative case study was carried out in a regional sports federation in Germany. The findings reveal that member clubs’ expectations can be represented using six reliable factors. The subsequent cluster analysis indicates four different expectation-based club types with heterogenous profiles. Based on the z-standardized factor values, the identified club types were labelled as follows: (1) “People Promoters” (32%), (2) “Undemanding” (22%), (3) “Competition-oriented Self-administrators” (23%) and (4) “Demanding Communicators” (23%). The extracted clusters were also reflected and validated by other structural and organizational characteristics of the sports clubs. The extracted types provide a first empirical step to identify different expectation schemes regarding services of sports federations. These schemes enable managers of sports federations to professionalize their service portfolios and, at the same time, to design services contributing to the development of sports clubs in a more targeted manner.